Elevated levels of IgA and IgG2 in individuals with chronic spinal cord injury. (3rd September 2022) - Shnawa, Aya; Lee, Samuel; Papatheodorou, Angelos; Gibbs, Katie; Stein, Adam; Morrison, Debra; Bloom, Ona
Abstract : Objectives: To determine circulating levels of antibodies (IgA, IgM, IgG1-4) in individuals with SCI as compared to uninjured individuals. Study Design: Prospective, observational study. Setting: Outpatient clinic of a Department of Physical Medicine and Rehabilitation and research institute in an academic medical center. Participants: Individuals with chronic (≥ 1 year from injury) SCI and uninjured individuals. Outcome Measures: Serum antibody titers were determined by commercial multiplex ELISA. Results: Blood samples were collected from individuals with chronic SCI ( N = 29, 83% males) and uninjured individuals ( N = 25, 64% males). Among participants with SCI, the distribution of American Spinal Injury Association Impairment Scale (AIS) grades was: A ( n = 15), B ( n = 2), C ( n = 4), D ( n = 8). Neurological levels of injury were: cervical ( n = 17), thoracic ( n = 10), and lumbar ( n = 2). IgA levels were significantly elevated in participants with SCI compared to uninjured participants (median: 1.98 vs. 1.21 mg/ml, P < 0.0001), with levels most elevated in individuals with motor complete injuries compared to uninjured participants (P < 0.0003). IgG2 antibodies were also significantly elevated in participants with SCI compared to uninjured participants (median: 5.98 vs. 4.37 mg/ml, P < 0.018). Conclusions: To our knowledge, this study provides the first evidence of elevated IgA, the antibody type most prevalent at respiratory, genitourinary and gastrointestinal tracts, common sites of infections in individuals with SCI. IgG2 levels were also elevated in individuals with SCI. These data support further investigations of IgA and other antibody types in individuals with chronic SCI, which may be increasingly important in the context of emerging novel infectious diseases such as SARS-CoV-2.